Analysis of Distance Education in India Implementing Universal Education: Examining the Perception of Students towards Distance Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Distance Learning will offer a high educational condition for individuals to share their insight and thoughts and build up their aptitudes. In the present study we study of distance education learning so we were interact with the student and to found the student’s psychology, what they think about the distance education system. For the statistical analysis of the study, Chi-Square Test for Independence will be used. Respondent who were from different age, gender, qualification, and employment groups have similar opinion they are agreed with the statement.